2018
DOI: 10.31117/neuroscirn.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Cellular function of satellite cells does not play a role in muscle weakness of adult Ts1Cje mice

Abstract: Down syndrome (DS) is a genetic condition resulting from triplication of human chromosome (HSA)21. Besides intellectual disability, DS is frequently associated with hypotonia. Satellite cells are the resident cells that provides robust and remarkable regenerative capacity to the skeletal muscles, and its population size has been reported to be disease-associated. However, little is known about the population size of satellite cells in DS and the association of its intrinsic cellular functionality and hypotonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Downregulation of Ifnar1 and Ifnar2 are expected to reduce JAK-STAT signalling pathway which in turn would promote myoblast renewal and regeneration processes [85]. However, a previous study of skeletal muscle stem cells (SMSCs) derived from Ts1Cje and control mice of the same age did not show any differences in the number SMSC as well as their differentiation capability in vitro [86]. Although the finding suggests no apparent differences in myogenesis during normal physiological state of Ts1CJe muscles, it does not preclude the potential involvement of Ifnar1 and Ifnar2 via JAK-STAT signalling pathway during early skeletal muscle development or regeneration state which will become obvious in aging subjects or during muscle injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of Ifnar1 and Ifnar2 are expected to reduce JAK-STAT signalling pathway which in turn would promote myoblast renewal and regeneration processes [85]. However, a previous study of skeletal muscle stem cells (SMSCs) derived from Ts1Cje and control mice of the same age did not show any differences in the number SMSC as well as their differentiation capability in vitro [86]. Although the finding suggests no apparent differences in myogenesis during normal physiological state of Ts1CJe muscles, it does not preclude the potential involvement of Ifnar1 and Ifnar2 via JAK-STAT signalling pathway during early skeletal muscle development or regeneration state which will become obvious in aging subjects or during muscle injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of physical disabilities, for example, can lead to poor mental health as a result of social factors such as disability-related discrimination and heighten risk for the development of mental disorders such as depression, anxiety and post-traumatic stress disorder [14]. Our review of past articles indicated that contributors to NeurosciRN are keen to understand and develop interventions for a wide variety of health conditions closely associated with functional disability ranging from stroke [15,16], to epilepsy [17][18][19][20][21], to neurodegenerative diseases [22] as well as Down's syndrome [23][24][25]. 'Functional disability' refers to how people with health conditions are prevented from engaging and participating in activities, roles and other aspects of their lives, which are of value to them.…”
Section: Open Access | Editorial Issn: 2576-828xmentioning
confidence: 99%